Diurnal, Seasonal, and Vertical Variability in Carbon Monoxide Levels at a Semi‐Urban Site in India. Issue 5 (31st March 2017) - Verma, Nidhi; Satsangi, Aparna; Lakhani, Anita; Kumari, Kandikonda Maharaj; Lal, Shyam
Abstract : In the present study, near‐surface carbon monoxide (CO) measurements were carried out at a semi‐urban site in Agra, India (27°10′N, 78°05′E), during March 2015 to February 2016. The study includes the diurnal, seasonal, and vertical variation of CO and the effect of meteorological parameters on its levels. The diurnal variation of CO was characterized by high levels during morning (9–10 am) and evening (10–11 pm) hours and low levels during the afternoon (3–5 pm). The morning and evening peak levels may be due to high emissions from traffic and low planetary boundary layer (PBL) height which prevents dispersion of pollutants. The low levels during afternoon hours may be due to increasing PBL height and loss through photochemical reactions. CO showed a distinct seasonal variation with highest levels in winter (770 ± 466 ppb) and lowest in monsoon (153 ± 122 ppb). The high levels in the winter season may be attributed to increased emissions from coal and wood burning used for heating in combination with stagnant weather conditions. The study also included latest retrievals of CO using Measurements of Pollution in the Troposphere (MOPITT) to define the vertical and seasonal variation of CO. The pattern of seasonal variation observed by ground level measurements was consistent with MOPITT surface CO levels. Abstract : The study is conducted at a semi‐urban site of India. The results indicate that the diurnal and seasonal variation of surface CO is strongly influenced by meteorological parameters. On the basis of satellite based measurements, seasonal variation of CO in lower troposphere is consistent with the surface measurements while in upper and middle troposphere seasonality is not distinct.